The Demand of Hospital Pharmacist Workforce in Past Eleven Years (2006-2016) and Forecasting Future Fifteen Years (2016-2030) at all Healthcare Institutions in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore hospital pharmacist’s workforce demand in past eleven years (2006-2016) and forecasting future fifteen years (2016-2030) at all hospitals of healthcare institutions in Saudi Arabia. Methods: It is a retrospective analysis of eleven years (2006-2016) of MOH hospital pharmacist workforce. All data were derived from Ministry of Health Statistical Year Books. It included pharmacist or clinical pharmacist’s workforces at hospitals in Kingdom of Saudi Arabia. The type of hospital included having bed capacity 50-1500 beds with Adults public hospitals, pediatrics and maternity hospitals, Psychiatric hospitals, Diabetic centers, Cardiology centers, Oncology Centers, Renal Dialysis Centers, and Medical cities. All calculations based on MOH workforce standards of hospitals population increases annually. The calculations done per each region for a total of twenty-one regions, the hospital beds distribution numbers, the ratio of pharmacist per bed, total number of demand pharmacist per each sector, the expected number of pharmacist requirement in the coming years 2016-2030 per each sectors across Saudi Arabia. Result: The total number of hospitals were 466 in the kingdom of Saudi Arabia, 274 (58.8%) Ministry of Health hospitals, 152 (32.6%) private hospitals, and 40 (8.6%) non-MOH governmental hospitals. Over the eleven years, the average numbers of hospitals were (423.45) with a range number of (384-467), and the total number was (467). The average numbers of hospital beds were (60,779.55) with a range number of (54,719-70,844), and the total number was (70,844). The average numbers of pharmacists per hospital were (10.31) with a range number of (8.63-14.04). The total average demand hospitals were (7,750.64) with range (7,628.80-7,609.80) with total number demand was (7,609.80) hospital pharmacists. The total demand hospital pharmacists at all sectors by the year 2030 will be (36,645.87) with range (25,794- 36,645.87). Conclusion: The highest demand for hospital pharmacists will be at MOH hospital sectors because of the large numbers of hospitals and many serving the population. Revision of hospital pharmacists’ jobs is mandatory and sharing with private hospitals is the requirement.
Keywords: Hospital pharmacist; Workforces; Manpower; Ministry of health; Saudi Arabia